Impact between the sociodemographic profile and the retirement age of professional handball players in the Asobal League - Jose Cuenca; Ana María Gallardo; Carlos Chavarría-Ortiz; Rafael Baena-González (Motricidade)
Sports retirement is something inherent to professional sports. Handball is a minority sport in which the most athletes have to continue their working life outside of the sport once they retire from it. The objective of this study was to analyze how age influences the different variables that affect the sports retirement process. The sample is made up of 95 professional handball players, all men, former members of the ASOBAL league and retired in the last 10 years. They have been administered a validated questionnaire. To analyze the results obtained from the questionnaire, a descriptive, relational and transversal study has been carried out. The retirement age is very polarized depending on the variable referred to. The variables level of education and professional status have no significant relationship with retirement age, however, marital status and offspring are significantly related.